Personalized Behavioral Feedback for Online Gamblers: A Real World Empirical Study - Auer, Michael M. (Front Psychol, 2016)
Responsible gambling tools (e.g., limit-setting tools, pop-up messages, and personalized feedback) have become increasingly popular as a way of facilitating players to gamble in a more responsible manner. However, relatively few studies have evaluated whether such tools actually work. The present study examined whether the use of three types of information (i.e., personalized feedback, normative feedback, and/or a recommendation) could enable players to gamble more responsibly as assessed using three measures of gambling behavior, i.e., theoretical loss (TL), amount of money wagered, and gross gaming revenue (GGR) (i.e., net win/loss). By manipulating the three forms of information, data from six different groups of players were analyzed. The participant sample drawn from the population were those that had played at least one game for money on the Norsk Tipping online platform (Instaspill) during April 2015. A total of 17,452 players were randomly selected from 69,631 players that fulfilled the selection criteria. Of these, 5,528 players participated in the experiment. Gambling activity among the control group (who received no personalized feedback, normative feedback or no recommendation) was also compared with the other five groups that received information of some kind (personalized feedback, normative feedback and/or a recommendation). Compared to the control group, all groups that received some kind of messaging significantly reduced their gambling behavior as assessed by TL, amount of money wagered, and GGR. The results support the hypothesis that personalized behavioral feedback can enable behavioral change in gambling but that normative feedback does not appear change behavior significantly more than personalized feedback.